Medical Eponym Angst. (June 2014) - Lawrence Abel, Ernest
<x content-type="archive" xml:space="preserve">Abstract</x> An eponym is a person, real or fictitious, after whom something has been named. Eponyms have been an integral part of medical nomenclature and history for centuries, but their continued use, including their spelling, is contentious. This article reviews the history of the term, disagreements concerning its lexical legitimacy, and arguments pro and con about their place in modern medical nomenclature. Despite all the legitimate reasons for dropping them, eponyms are so deeply rooted in medicine that they are here to stay for the foreseeable future.